Auto-reinforce magnetic flywheel as recent advancement of automobile flywheel - Akbar, A.R. (EDP Sciences, 2014)
A new feature for flywheel energy storage device is proposed, considering the deficiencies on existing technology. This feature is introduced as auto-reinforce performance which means an ability to recover the kinetic energy after speed-down occurred as impact of sudden loading or sudden braking. The performance will significantly keep longer the stored energy of a flywheel device. This novel concept of flywheel is engineered by installing a number of Permanent Magnets (PM). The magnetism configuration such magnetic strength, magnetic energy density, pole direction, geometry, and dimension are influential parameters to its performance. By executing Finite Element Magnetic Modeling, it is possible to predict the design parameters such magnetic force and magnetic torque. Finally by evaluating these mechanical parameters, the key performance of this device such as percentage of energy reinforcement and percentage of discharge elongation can be predicted for prototyping references. Â© 2014 Owned by the authors, published by EDP Sciences.